Environmental and climatic proxies for the Cañadón Asfalto and Neuquén basins (Patagonia, Argentina): review of middle to upper jurassic continental and near coastal sequences - Volkheimer, Wolfang (2015)
In this review, we include several proxies (sedimentology, palynology, invertebrates) from the Cañadón Asfalto and Neuquén basins, to infer the environments and regional climatic context during the Middle to Late Jurassic of Patagonia. In central Patagonia, early in the Middle Jurassic, and associated with a magmatic arc, began the sedimentary fi lling of Jurassic continental sub-basins in the Cañadón Asfalto Basin. Lacustrine and fl uvio-deltaic sediments, bearing a continental Middle Jurassic palynobiota, correspond to the Las Chacritas Member, while the sediments and palynobiota from the Late Jurassic Puesto Almada Member (both in the Cañadón Asfalto Formation) indicate a palustrine wetland subenvironment immersed within an arid macroenvironment. Paleoinvertebrates (conchostracans and sponges) of this formation suggest wet-dry cycles in the water bodies they inhabited. The sedimentological information together with the continental and coastal palynomorph assemblages of the back arc Neuquén Basin, allowed distinguishing a complete regressive-transgressive sequence for the Middle Jurassic Lajas Formation. For the Upper Jurassic in this basin, the thick gypsum and anhydrite deposits of the evaporitic coastal Auquilco Formation correlate with extended deposits of eolian sandstones corresponding to the Botucatú paleodesert, and a saltmarsh environment is inferred from the palynofl ora. The palynologic associations from both basins indicate a regional warm climate with seasonal aridity. Climatic conditions would have been drier in the continental interior (Cañadón Asfalto Basin), with strongly seasonally distributed temperatures, and moister in the western coast of the continent (Neuquén Basin), during the marine transgressions.